Assessment of Farmers Perception about Climate Change Impact and Adaptation Strategies Use for Tomato Production in The Gambia - Sanneh, Lamin; Babana, Amadou Hamadoun; Yaffa, Sidat (Journal of Agricultural Studies, 2022)
Tomato production in The Gambia is ranked second after onion in terms of production acreage among vegetables. Tomatoes are major sources of lycopene, a dietary carotenoid found in high concentration in processed tomato products. The crop is high in vitamin AB and C and also contain good amount of potassium, iron and phosphorus. Fresh tomatoes and canned types such as concentrates puree and paste are increasingly in demand in West Africa where they form an essential part of the diet. The study investigated farmer’s perception about climate change impact and adaptation strategies use for tomato production in the Gambia through survey. The survey was conducted in the West Coast Region originally known as Western Division situated in the west near the capital. Random sampling was used for the selection of farmers for the individual survey and focus group discussions. The findings concluded that significant number of the tomato growers are aware and also strongly believed that climate change is existing. Constant increase in temperature and decrease in rainfall, an unpredictable rainfall pattern and prolonged drought among others served as evidences. Large number of respondents said to have experienced climate change effects for more than five years while minority indicated about 5-10years of experienced. Most of the tomato growers said they became to know about climate change through personal experience. Climate change causes severe dropping of flowers by rain and wind and rotting of tomato fruits as well as pest attack at the reproductive stage. For the case of adaptation strategies, great numbers of the farmers are using synthetic pesticide to control insect pests e.g., red spider mites, planting of trees (wind breakers) to reduce heavy wind speed and application of large quantity of fertilizers to improve the soil fertility.